Lei anticorrupção: o acordo de leniência e seus principais aspectos - Abdo, Ricardo Camarotta (2016)
The present dissertation aims to analyze the institute of the leniency agreement, as established in the Law nº 12.846, of August 1, 2013, also known as the Brazilian Clean Company Law, and its framework as a contemporary measure of the public administration by consensus, not mandatory. For such purpose, we will initially analyze some basic concepts to establish assumptions for the development of this work. Later on, we will analyze the Clean Company Act Law as a whole. Finally, and doing so, we will focus on the analysis of the leniency agreement encompassing its main aspects and controversial issues linked to the institute